Single-cell new RNA sequencing reveals principles of transcription at the resolution of individual bursts - Ramsköld, Daniel; Hendriks, Gert-Jan; Larsson, Anton J. M.; Mayr, Juliane V.; Ziegenhain, Christoph; Hagemann-Jensen, Michael; Hartmanis, Leonard; Sandberg, Rickard (Nature cell biology, 2024)
Analyses of transcriptional bursting from single-cell RNA-sequencing data have revealed patterns of variation and regulation in the kinetic parameters that could be inferred. Here we profiled newly transcribed (4-thiouridine-labelled) RNA across 10,000 individual primary mouse fibroblasts to more broadly infer bursting kinetics and coordination. We demonstrate that inference from new RNA profiles could separate the kinetic parameters that together specify the burst size, and that the synthesis rate (and not the transcriptional off rate) controls the burst size. Importantly, transcriptome-wide inference of transcriptional on and off rates provided conclusive evidence that RNA polymerase II transcribes genes in bursts. Recent reports identified examples of transcriptional co-bursting, yet no global analyses have been performed. The deep new RNA profiles we generated with allelic resolution demonstrated that co-bursting rarely appears more frequently than expected by chance, except for certain gene pairs, notably paralogues located in close genomic proximity. Altogether, new RNA single-cell profiling critically improves the inference of transcriptional bursting and provides strong evidence for independent transcriptional bursting of mammalian genes. Ramskold, Hendriks, Larsson et al. use deep single-cell profiling of newly transcribed RNA to uncover the kinetics and dynamics of transcriptional bursting at allelic resolution in primary mouse cells.